Navigating the uncharted waters: the complexities and challenges of auditing cryptocurrency / Norizam Ahmad @ Muhammad - Ahmad @ Muhammad, Norizam (Fakulti Perakaunan, 2023)
Cryptocurrency has emerged as a revolutionary digital asset class that has gained significant traction in the global financial landscape. As the popularity of cryptocurrencies continues to soar, so does the need for effective auditing practices to ensure their transparency, reliability, and security. However, auditing cryptocurrency presents a unique set of challenges that differ from traditional financial audits. This article delves into the challenges faced by auditors in assessing the financial statements and controls of cryptocurrency entities, shedding light on critical aspects that must be considered.